Chloramphenicol – A Potent Armament Against Multi-Drug Resistant (MDR) Gram Negative Bacilli? - Sood, Smita (J Clin Diagn Res, 2016)
INTRODUCTION: Multidrug-resistant gram-negative bacteria cause infections which are hard to treat and cause high morbidity and mortality. Due to limited therapeutic options there is a renewed interest upon older antimicrobials which had fallen into disuse as a result of toxic side effects. One such antibiotic is chloramphenicol which was sidelined due to reports linking its use with the development of aplastic anaemia. AIM: A study was conducted to evaluate the susceptibility of chloramphenicol in light of the emerging problem of multi-drug resistant gram negative bacteria (MDR GNB). MATERIALS AND METHODS: A total of 483 MDR GNB of the 650 consecutive Gram Negative Bacteria isolated from various clinical samples of patients admitted at a tertiary care hospital in Jaipur between January-June 2014 were screened for chloramphenicol susceptibility by the disc diffusion method as per CLSI guidelines. RESULTS: The MDR GNB isolates were obtained from 217 (45%) urine, 163 (34%) from respiratory samples, 52(11%) from pus, 42 (9%) from blood and 9 (2%) from body fluids. A 68% of the MDR GNB isolates were found to be sensitive to chloramphenicol. CONCLUSION: Clinicians should always check for the local susceptibility of Gram-negative bacteria to chloramphenicol. This antibiotic has a potential to play a role in the therapeutic management of infections due to MDR GNB pathogens.